Expression of voltage-dependent anion channels in endometrial cancer and its potential prognostic significance. Issue 8 (August 2020) - Jóźwiak, Paweł; Ciesielski, Piotr; Forma, Ewa; Kozal, Karolina; Wójcik-Krowiranda, Katarzyna; Cwonda, Łukasz; Bieńkiewicz, Andrzej; Bryś, Magdalena; Krześlak, Anna
The exchange of metabolites between mitochondria and cytosol occurs through pores formed by voltage-dependent anion channel proteins. Voltage-dependent anion channels appear to be master regulators of mitochondrial bioenergetics and the intracellular flow of energy. Deregulation of voltage-dependent anion channels expression is thought to be related to mitochondrial dysfunction in cancer. The aim of this study was to investigate the mRNA and protein expression levels of VDAC1, VDAC2, and VDAC3 in relation to clinicopathological characteristics of endometrial cancer as well as the prognostic significance of voltage-dependent anion channels expression for overall survival. VDAC1 and VDAC3 expressions were significantly higher in cancer compared to normal tissues. Kaplan–Meier analysis indicated that high expression of all VDAC genes or high VDAC2 protein level predicted poor overall survival. Multivariate analysis identified the VDAC1 and VDAC2 mRNA levels as well as VDAC2 protein level as independent prognostic factors. Our results suggest that increased expression of voltage-dependent anion channels correlates with tumor progression and may serve as a potential prognostic biomarker in endometrial cancer.